Guided Inquiry Learning Model with Socio Scientific Issue Approach: A Systematic Literature Review - Syafira, Annisa; Miterianifa, Miterianifa (Journal of Natural Science and Integration, 2025)
This study aims to explore the application of the guided inquiry learning model integrated with the Socio-Scientific Issues (SSI) approach through a Systematic Literature Review (SLR) following the PRISMA framework. The review employed the Publish or Perish software to extract and analyze relevant scientific articles published between 2018 and 2024. The data analysis involved identifying, screening, and synthesizing studies aligned with the research focus. From an initial pool of 1,755 articles, only 9 met the inclusion criteria. The findings indicate that the guided inquiry model combined with the SSI approach positively influences various educational outcomes, including students’ science process skills, scientific argumentation abilities, critical thinking, and the overall quality of the learning environment. Despite its potential benefits, the integration of guided inquiry and SSI remains underexplored in existing literature, revealing a significant research gap. This underscores the relevance and urgency of further empirical investigations in this area. The positive correlation observed in the selected studies highlights the potential of this pedagogical integration to foster more meaningful and contextually rich science education. Consequently, this topic presents a valuable avenue for future research and innovation in science teaching and learning. Keywords: guided inquiry, socio scientific issues, systematic literature review